(untitled) (Annals of Medical Research, 2021)
Aim: To determine the area, density and morphology of physiologic pineal gland calcification in the preadolescents and adolescents using computed tomography and to evaluate correlations with age and sex.Material and Methods: This retrospective study evaluated 220 cases (110 males, 110 females) with ages ranging from 7-17 years (mean age: 12±3.17). Cases were divided into two groups according to age of 7-12 years (n=120, preadolescent) and 13-17 years (n=100, adolescent). Morphology (homogeneous-heterogeneous), area (mm2) and density (Hounsfield Units [HU]) of pineal calcifications were investigated on computed tomography. Comparisons were made between age groups and sex in terms of these variables.Results: This study found pineal calcification frequency was 50%, 35% and 67% in all cases, preadolescents, and adolescents, respectively. According to morphology, 60.9% of calcifications were homogeneous and 39.1% were heterogeneous. Median calcification area and density values were 8.50 (6-15) mm2 and 67 (50-109.75) HU, and 7 (4.75-14.25) mm2, and 67 (53.25-87.75) HU, for males and females, respectively, with no significant difference identified between the sexes (p=0.353 and p=0.463, respectively). Median calcification area in the preadolescent and adolescent age groups was 7 (6-12) and 10 (5-18) mm2, with no significant difference identified between the groups (p=0.175). Median density values were 70 (56-109) HU for adolescents and this was high compared to preadolescents (59 [47-78] HU) (p=0.005). Conclusion: Physiologic pineal calcification frequency, area, density and morphology were revealed for preadolescent and adolescents. These values may be used as qualitative and quantitative reference data for differentiation of normal/abnormal pineal calcification in routine practice.